Pengembangan Penilaian Pengetahuan Bahasa Arab Berbasis Test Objektif di Pusat Pendidikan Islam Muharrikun Najaah - Rif’atul Fadhilah (The Arabic Education Department Postgraduate Programs, UIN Sultan Maulana Hasanuddin Banten in Partnership with PPJKBA Indonesia, 2021)
The purpose of this study is to demonstrate and characterize: 1) Development of an assessment of Arabic knowledge that is applied to Arabic learning at the Muharrikun Najaah Islamic Education Center 2) The process of implementing an Arabic knowledge assessment at the Muhrrikun Najaah Islamic Education Center? This study uses a descriptive qualitative approach, which is located at the Muharrikun Najaah Islamic Education Center, Klaten. Where in this case the researcher understands the phenomena that occur and to maintain the weakness of the data, the data collection techniques used are direct observation, interviews and documentation. The research subject is the principal, and the informants are students, and Arabic language teachers. And to test the reliability of the data using source triangulation, then analyzed with an interactive model Miles and Hubermant: Data collection, data boundaries, data presentation, and drawing conclusions. Based on the results of the research conducted, it shows that: 1) Development of the Arabic Barasa knowledge assessment at PPIMN is carried out by assessing students not only in terms of attitudes but in terms of students’ knowledge in implementing what they have learned during the learning process in everyday life. -day, 2) The process of implementing knowledge assessment at the Muharrikun Najaah Islamic Education Center is carried out sequentially starting from planning, implementing, processing, and evaluating using various assessments.